TEKNOLOGI BUDIDAYA MGORS SOLUSI MENGHASILKAN SAYURAN SEHAT DAN BERGIZI SECARA BERKELANJUTAN - Sarijan, Abdullah; Noer, Elly; Kusumah, Rangga; Aulia Farahningtyas, Diva; Syari, Halana; B Majid, M. Asvad; DA Sarijan, Kurniawan; Ramadhani, Fitri; Anjani, Sri (Batara Wisnu : Indonesian Journal of Community Services, 2024)
This community service activity aims to increase the community's understanding and skills in cultivating vegetables using MGorS (Microgreen or Sprout) technology at the ABBA Orphanage and Annajah Yamra Islamic Boarding School, Merauke Regency. Considering the increasing use of chemicals in conventional agriculture which have the potential to contaminate harvests, this activity was carried out to provide a solution by prioritizing healthy and sustainable cultivation techniques. Through socialization, training, planting and maintenance, evaluation, and coaching, participants are guided in two important aspects: production and management. The evaluation results showed that the ABBA Orphanage scored 75 in its ability to produce vegetables independently. At the same time, the Annajah Yamra Islamic Boarding School managed to achieve a score of 80. Although both partners achieved targets in several aspects, there was a lack of understanding regarding sustainability in cultivation. Recommendations for additional training and mentoring in the field are proposed to improve learning and future application of MGorS technology.